Moulting Greylag Geese Anser anser on the Danish island of Saltholm; numbers, phenology, status and origins - Fox, A D; Kahlert, J; Ettrup, H; Nilsson, L; Hounisen, J P (Wildfowl, 1995)
In recent years, the Danish island of Saltholm has become the second-most important moulting site for Greylag Geese in northwest Europe. Numbers present on the island increased rapidly towards the end of May and peaked in mid-June, with a maximum of 9,100 Greylags counted in 1994. Goose numbers declined rapidly after early July, although there was a lag between their departure from Saltholm and the build-up of numbers at monitored resorts in adjacent parts of Sweden. During the settlement phase, Greylags fed for a substantial part of daylight hours, but during the peak of moult, they fed exclusively at night when they came ashore from daytime offshore roosting areas. Based on the presence of individually marked birds, the moulting population was mainly composed of young non-breeding birds from adjacent areas in Denmark and Sweden. It is suggested that Saltholm has become an important moulting site because of the availability of plentiful food resources, the absence of terrestrial predators and restricted human activity. In addition, the population from which the Saltholm birds are recruited has increased, and it is suggested that competition in the breeding areas may have displaced younger, non-breeding individuals to this new moult site.